SUPPRESSOR OF PHYTOCHROME B4-#3 Represses Genes Associated with Auxin Signaling to Modulate Hypocotyl Growth . Issue 4 (24th June 2016) - Favero, David S.; Jacques, Caitlin N.; Iwase, Akira; Le, Kimberly Ngan; Zhao, Jianfei; Sugimoto, Keiko; Neff, Michael M.
Abstract : SOB3 modulates seedling elongation by repressing the expression of genes associated with auxin signaling. Abstract: Developing seedlings are well equipped to alter their growth in response to external factors in order to maximize their chances of survival. SUPPRESSOR OF PHYTOCHROME B4-#3 (SOB3) and other members of the AT-HOOK MOTIF CONTAINING NUCLEAR LOCALIZED (AHL) family of transcription factors modulate the development of Arabidopsis ( Arabidopsis thaliana ) by repressing hypocotyl elongation in young seedlings growing in light. However, the molecular mechanism behind how AHLs influence seedling development is largely unknown. We have identified genes associated with auxin-mediated hypocotyl elongation as downstream targets of SOB3. We found that YUCCA8 ( YUC8 ) as well as members of the SMALL AUXIN UP-REGULATED RNA19 ( SAUR19 ) subfamily were down-regulated in the short-hypocotyl, gain-of-function SOB3-D mutant and up-regulated in the dominant-negative, tall-hypocotyl sob3-6 mutant. SOB3-D and sob3-6 hypocotyls also exhibited altered sensitivity to the polar auxin transport inhibitor N -1-napthylphthalamic acid, suggesting a critical connection between auxin and the modulation of seedling elongation by SOB3 . Finally, we found that overexpression of GREEN FLUORESCENT PROTEIN-SAUR19 in the SOB3-D line partially rescued defects in hypocotyl elongation, and SOB3 bound directly to the promoters of YUC8 and SAUR19 subfamily members. Taken together, these data indicate that SOB3 modulates hypocotyl elongation in young seedlings by directly repressing the transcription of genes associated with auxin signaling.